Negative electrode for lithium secondary battery, method for producing the same, and lithium secondary battery including the same

By using lithium-magnesium aluminum alloy film as the negative electrode material for lithium sulfur batteries, the problems of lithium branch growth and solid electrolyte boundary layer instability are solved, and the cycle life and electrochemical efficiency of the battery are improved.

JP2025511505APending Publication Date: 2025-04-16LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024553488
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-30
Filing Date
2023-08-31
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

In existing lithium-sulfur batteries, the high chemical and electrochemical activity of lithium metal negative electrode materials leads to instability of the solid electrolyte boundary layer, leading to problems such as lithium branch growth, internal short circuits and reduced battery capacity and cycle life.

Method used

Lithium-magnesium aluminum (Li-Mg-Al) alloy is used as the negative electrode material, and is applied to the negative electrode active layer through the film form of the alloy, and the content and weight ratio of magnesium and aluminum are controlled to improve the elastic modulus and tensile strength of the alloy.

Benefits of technology

It improves the cycle life and electrochemical efficiency of lithium sulfur batteries, reduces the growth of lithium branches and the occurrence of internal short circuits, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511505000001_ABST
    Figure 2025511505000001_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery including a lithium-magnesium-aluminum alloy, a method for producing the same, and a lithium secondary battery including the same, such as a lithium-sulfur battery. A lithium secondary battery including the negative electrode according to the present invention, such as a lithium-sulfur battery, exhibits superior battery life characteristics compared to batteries using the conventional negative electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same.

[0002] This application claims priority to Korean Patent Application No. 10-2022-0110408 filed on August 31, 2022, Korean Patent Application No. 10-2023-0082211 filed on June 26, 2023, and Korean Patent Application No. 10-2023-0114846 filed on August 30, 2023, and the contents disclosed in the specification and drawings of such applications are incorporated herein in their entirety. [Background technology]

[0003] As the range of applications for lithium secondary batteries expands beyond portable electronic devices to include electric vehicles (EVs) and energy storage systems (ESS), the demand for high-capacity, high-energy density, and long-life lithium secondary batteries is increasing.

[0004] Among the various lithium secondary batteries, the lithium-sulfur battery is a battery system that uses a sulfur compound containing a sulfur-sulfur (SS) bond as the positive electrode active material and lithium metal, a carbon-based material capable of intercalating / deintercalating lithium ions, silicon or tin that forms an alloy with lithium metal, etc. as the negative electrode active material.

[0005] Lithium-sulfur batteries have the advantage that sulfur, the main positive electrode active material, has a low atomic weight, is abundant in resources, is inexpensive, non-toxic, and environmentally friendly.

[0006] In addition, lithium-sulfur batteries use a conversion reaction between lithium ions and sulfur at the positive electrode (S8+16Li + +16e -The theoretical specific capacity of the lithium-sulfur battery is 1,675mAh / g, derived from lithium ion battery (Li2S) and 2,600Wh / kg when lithium metal is used as the anode. The theoretical energy density of the lithium-sulfur battery is much higher than that of other battery systems (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000Wh / kg, Na-S battery: 800Wh / kg, lithium-ion battery: 250Wh / kg), and the lithium-sulfur battery has attracted attention among the secondary batteries developed so far due to its high capacity, environmental friendliness, and low price.

[0007] In addition, in the case of lithium-sulfur batteries, when lithium metal is used as the negative electrode active material, the theoretical specific capacity is very high at 3,860mAh / g, and the standard hydrogen electrode (SHE) is also very low at -3.045V, making it possible to realize a battery with high capacity and high energy density. Therefore, research on lithium-sulfur batteries as a next-generation battery system is being actively conducted.

[0008] However, lithium metal, which is an anode active material, has high chemical / electrochemical reactivity and easily reacts with the electrolyte, so a type of protective film called a solid electrolyte interface layer (SEI) is formed on the surface of the anode. The solid electrolyte interface layer formed in this way can suppress direct reaction between the electrolyte and lithium metal and ensure a certain level of stability for the anode active material containing lithium metal, so attempts have been made to form such an SEI layer stably and uniformly on the surface of lithium metal.

[0009] However, in the case of lithium-sulfur batteries, when the negative electrode active material is lithium metal, even if an SEI layer is formed as described above, it is difficult to maintain the SEI layer constant because the electrochemical reaction of the battery continues to occur on the surface of the lithium metal. In addition, the SEI layer formed by the reaction between the electrolyte and lithium metal has a weak mechanical strength, so as the battery is charged and discharged, its structure collapses, causing a local current density difference and forming lithium dendrites on the surface of the lithium metal. In addition, the lithium dendrites thus formed not only increase the physical and chemical instability of the lithium secondary battery by inducing an internal short circuit and inactive lithium (dead lithium) in the battery, but also reduce the battery capacity and cycle life. In addition, the positive electrode active material is dissolved in the form of lithium polysulfide (LiPS) and migrates to the negative electrode to form lithium sulfide by-products, which may cause loss of the positive electrode active material / passivation of the negative electrode and undesired side reactions.

[0010] Due to the high instability of lithium metal and the problem of lithium dendrite formation, various attempts have been made to solve these problems.

[0011] For example, Patent Document 1 discloses that the loss of electrolyte and the formation of dendrites can be prevented by forming a protective layer made of a polymer matrix that can accumulate an electrolyte while protecting the negative electrode on the surface of a negative electrode active material layer containing lithium metal and a lithium alloy.

[0012] Patent Document 2 discloses that the stability and life characteristics of a lithium secondary battery can be improved by suppressing the growth of lithium dendrites by introducing an absorbent material for lithium dendrites into a polymer protective film formed on the surface of lithium metal.

[0013] Although the prior art has been able to suppress the reaction between the electrolyte and lithium metal or the formation of lithium dendrites to some extent, the effect is not sufficient, and there is a problem of deterioration such as hardening or swelling of the protective layer as the battery is charged and discharged. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] Korean Patent Publication No. 2016-0034183 [Patent Document 2] Korean Patent Publication No. 2016-0052351 Summary of the Invention [Problem to be solved by the invention]

[0015] The present invention has been made in view of the above problems, and there is a need to develop a lithium metal negative electrode for a lithium secondary battery that overcomes the shortcomings of the prior art, in particular a lithium-based material for forming the negative electrode of a lithium secondary battery that is suitable for improving the life and electrochemical efficiency of the battery. [Means for solving the problem]

[0016] The above-mentioned object can be achieved by the invention as defined in the independent claims, and various further embodiments are suggested by the dependent claims and / or the detailed description of the invention.

[0017] According to a first aspect of the present invention, there is provided a negative electrode for a lithium secondary battery, the negative electrode comprising a Li-Mg-Al alloy. In one embodiment of the present invention, the Li-Mg-Al alloy may have the form of a thin film.

[0018] According to a second aspect of the present invention, in the first aspect, the content of magnesium (Mg) in the lithium-magnesium-aluminum alloy may be 0.1 to 50 wt% with respect to a total of 100 wt% of the lithium-magnesium-aluminum alloy.

[0019] According to a third aspect of the present invention, in the first or second aspect, the content of aluminum in the lithium-magnesium-aluminum alloy may be 0.01 to 10 wt % based on the total weight of the lithium-magnesium-aluminum alloy.

[0020] According to a fourth aspect of the present invention, in any one of the first to third aspects, the weight ratio of magnesium to aluminum in the lithium-magnesium-aluminum alloy can be controlled within a range of 2:1 to 20:1.

[0021] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the negative electrode may include a thin-film lithium-magnesium-aluminum alloy, and the alloy may have a thickness of 0.1 μm to 200 μm.

[0022] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the lithium-magnesium-aluminum alloy may have an elastic modulus of 400 MPa or more, or a tensile strength of 1.5 MPa or more.

[0023] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the lithium-magnesium-aluminum alloy is an EM according to the following formula (1): d Value is 600MPa cm 3 / g or more.

[0024] Equation (1)EM d =EM alloy / d alloy Here, E.M. alloy is the elastic modulus of the alloy according to the ASTM standard, and d alloy means the density of an alloy, the density of said alloy means the mass of the alloy per unit volume of the alloy, and said volume is the apparent volume of the alloy.

[0025] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the lithium-magnesium-aluminum alloy may have a monolithic nature.

[0026] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the lithium-magnesium-aluminum alloy may have magnesium and aluminum uniformly distributed in the alloy.

[0027] According to a tenth aspect of the present invention, there is provided an anode for a lithium secondary battery, the anode comprising an alloy comprising a combination of lithium and one or more additional metals, the alloy having an elastic modulus of 400 MPa or greater.

[0028] An eleventh aspect of the present invention relates to a negative electrode for a lithium secondary battery, the negative electrode comprising an alloy of lithium in combination with one or more additional metals, the alloy being an EM according to formula (1): d The value is 600MPa cm 3 / g or more.

[0029] Equation (1)EM d =EM alloy / d alloy

[0030] Here, E.M. alloy is the elastic modulus of the alloy according to the ASTM standard, and d alloy means the density of an alloy, the density of the alloy means the mass of the alloy per unit volume of the alloy, and the volume is the apparent volume of the alloy.

[0031] According to a twelfth aspect of the present invention, in the tenth or eleventh aspect, the additional metal may include one or more of magnesium and aluminum.

[0032] According to a thirteenth aspect of the present invention, in any one of the tenth to twelfth aspects, the additional metal includes at least one of magnesium and aluminum, wherein the content ratio of magnesium to aluminum is 2:1 to 20:1 by weight.

[0033] The present invention relates to a lithium secondary battery. According to a fourteenth aspect of the present invention, the lithium secondary battery includes a negative electrode according to any one of the first to thirteenth aspects.

[0034] According to a fifteenth aspect of the present invention, in the fourteenth aspect, the lithium secondary battery further includes a separator and an electrolyte.

[0035] According to a sixteenth aspect of the present invention, in the fourteenth or fifteenth aspect, the lithium secondary battery is a lithium-sulfur battery in which a positive electrode active material contains sulfur (S) and / or a sulfur (S) compound.

[0036] According to a seventeenth aspect of the present invention, there is provided a method for producing an anode for a lithium secondary battery according to any one of the first to eleventh aspects, the method comprising the steps of melting metallic lithium to obtain a first molten material, adding metallic magnesium and metallic aluminum to the lithium melt to obtain a second melt; maintaining the second molten material at a temperature of 200° C. or more to alloy the second molten material; and cooling the second molten material obtained from the alloying step to obtain a lithium-magnesium-aluminum alloy.

[0037] According to an eighteenth aspect of the present invention, in the seventeenth aspect, the alloy may be obtained in an ingot form, and the method may further include a step of thinning the ingot into a plate-like structure having a predetermined thickness. Effect of the Invention

[0038] A lithium secondary battery, such as a lithium-sulfur battery, including the anode according to the present invention exhibits superior battery life characteristics compared to batteries using the anodes of the prior art.

[0039] A lithium secondary battery, such as a lithium-sulfur battery, including the anode according to the present invention exhibits superior battery efficiency characteristics compared to batteries using the anodes of the prior art.

[0040] The following drawings attached to this specification are for illustrating preferred embodiments of the present invention, and serve to further understand the technical idea of ​​the present invention together with the detailed description of the invention, so the present invention should not be interpreted as being limited to only the matters described in the drawings. In addition, the shape, size, scale, ratio, etc. of the elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0041] [Figure 1] 1 shows the cycle life of the lithium-sulfur pouch batteries of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. [Diagram 2] 1 shows the coulombic efficiency of the lithium-sulfur pouch batteries of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. [Diagram 3] 1 shows the elastic modulus of the negative electrode materials according to Production Example 1, Production Example 4, and Comparative Example 1, and the negative electrode material of the Comparative Example. [Figure 4] 1 is a photograph showing an example of a punch for punching a test piece used in measuring the elastic modulus. [Diagram 5] 1 is a SEM image of a cross section of a negative electrode obtained in Example 1 of the present invention. [Figure 6] 4 is a result of EDS elemental analysis of a cross section of the negative electrode obtained in Example 1 of the present invention, showing the distribution of magnesium in the negative electrode. [Figure 7] 4 is a result of EDS elemental analysis of a cross section of the negative electrode obtained in Example 1 of the present invention, showing the distribution of aluminum in the negative electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0042] The terms and words used in this specification and the claims should not be interpreted limitedly to their ordinary or dictionary meanings, but should be interpreted in terms of meanings and concepts according to the technical ideas of the present invention, and should be based on the principle that the inventors themselves can appropriately define the concepts of terms in order to best describe the invention.

[0043] Unless otherwise limited, the detailed description defining or embodying the elements is applicable to all inventions and is not limited to the description of a particular invention, i.e., even if elements are disclosed individually in this specification, they may be considered to disclose an embodiment in which the elements are combined.

[0044] The terms used in this specification are merely used to describe specific embodiments and do not limit the present invention. Unless otherwise specified in the context, the singular expression includes the plural expression.

[0045] Also, in this specification, the terms "comprise" or "have" are intended to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, but do not exclude the possible presence or addition of one or more other features, number, step, operation, component, part, or combination thereof. The term "comprise" expressly includes the meanings of "consist of" and "essentially comprising", even if not expressly limited thereby.

[0046] As used herein, the term "essentially comprises" means "comprises at least 70%", preferably "comprises at least 80%", and most preferably "comprises at least 90%". When referring to the amount of a component of a mixture of substances, % means weight % (wt%) relative to the total weight of each mixture, unless otherwise stated. For example, a material that essentially comprises polyethylene comprises polyethylene in an amount of 70 wt% or more based on the total weight of the material.

[0047] In addition, the terms "about" and "substantially" used in this specification are used to mean "... or approximately..." given the tolerances of manufacturing and materials inherent in the stated circumstances, and are used to prevent infringers from infringing rights who attempt to unfairly take advantage of the content of the present invention in which precise or absolute numerical values ​​are recited to help understand the content of the present invention.

[0048] As used herein, "A and / or B" means "A or B, or all of these."

[0049] The term "composite" as used herein means a material in which two or more materials are combined to form physically and chemically distinct phases, thereby exhibiting a more effective function.

[0050] As used herein, the term "polysulfide" refers to a polysulfide ion (S x 2- , x=1~8) and Lithium polysulfide (Li2S x or LiS x - , X=1~8) is a concept that includes all of these.

[0051] It should be noted that the negative electrode referred to in this specification may also be referred to as the anode.

[0052] The present invention will now be described in more detail.

[0053] The present invention provides an anode for a lithium secondary battery, comprising a lithium-magnesium-aluminum alloy. In a specific embodiment of the present invention, the alloy may be introduced into the anode in the form of a thin film, and the anode may be formed from only the lithium-magnesium-aluminum alloy thin film, or may be formed in a form in which the alloy thin film is bonded to a current collector, preferably in a form in which the current collector and the alloy thin film are directly bonded to each other.

[0054] The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.1% by weight or more. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.5% by weight or more. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 1% by weight or more. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 2% by weight or more. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 3% by weight or more. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 4% by weight or more. Such an amount of Mg in the alloy is desirable in terms of the life and efficiency of the negative electrode.

[0055] The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 50% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 40% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 30% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 25% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 20% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 15% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 12.5% ​​or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 10% or less by weight. The content of magnesium in the lithium-magnesium-aluminum alloy may be 7.5% by weight or less, based on the total weight of the lithium-magnesium-aluminum alloy. The content of magnesium in the lithium-magnesium-aluminum alloy may be 6% by weight or less, based on the total weight of the lithium-magnesium-aluminum alloy. Such an amount of magnesium (Mg) in the alloy is desirable in terms of the life and efficiency of the negative electrode.

[0056] The content of magnesium in the lithium-magnesium-aluminum alloy may be 0.1-50% by weight based on the total weight of the lithium-magnesium-aluminum alloy. The content of magnesium in the lithium-magnesium-aluminum alloy may be 0.5-30% by weight based on the total weight of the lithium-magnesium-aluminum alloy. The content of magnesium in the lithium-magnesium-aluminum alloy may be 1-20% by weight based on the total weight of the lithium-magnesium-aluminum alloy. The content of magnesium in the lithium-magnesium-aluminum alloy may be 2-10% by weight based on the total weight of the lithium-magnesium-aluminum alloy. The content of magnesium in the lithium-magnesium-aluminum alloy may be 3-7% by weight based on the total weight of the lithium-magnesium-aluminum alloy. The content of magnesium in the lithium-magnesium-aluminum alloy may be 4-6% by weight based on the total weight of the lithium-magnesium-aluminum alloy. For example, it may be about 5% by weight. Such an amount of Mg in the alloy is desirable in terms of the life and efficiency of the negative electrode.

[0057] The content of aluminum (Al) in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.01 wt% or more. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.05 wt% or more. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.1 wt% or more. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.2 wt% or more. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.3 wt% or more. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.4 wt% or more. Such an amount of Al in the alloy is desirable in terms of the life and efficiency of the negative electrode.

[0058] The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 5% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 4% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 3% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 2.5% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 2% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 1.5% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 1.25% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 1% by weight or less. The content of aluminum in the lithium-magnesium-aluminum alloy may be 0.75 wt% or less relative to the total weight of the lithium-magnesium-aluminum alloy. The content of aluminum in the lithium-magnesium-aluminum alloy may be 0.6 wt% or less relative to the total weight of the lithium-magnesium-aluminum alloy. Such an amount of Al in the alloy is desirable in terms of the life and efficiency of the negative electrode.

[0059] The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.01-5 wt%. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.05-3 wt%. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.1-2 wt%. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.2-1 wt%. The content of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.3-0.7 wt%. The amount of aluminum in the lithium-magnesium-aluminum alloy relative to the total weight of the lithium-magnesium-aluminum alloy may be 0.4-0.6 wt%. For example, it may be about 0.5 wt%. Such an amount of Al in the alloy is desirable in terms of the life and efficiency of the negative electrode.

[0060] On the other hand, the weight ratio of magnesium to aluminum in the lithium-magnesium-aluminum alloy is 2:1 to 20:1. The weight ratio of aluminum to magnesium in the lithium-magnesium-aluminum alloy is 3:1 to 17.5:1. The weight ratio of magnesium to aluminum in the lithium-magnesium-aluminum alloy is 4:1 to 16:1. The weight ratio of aluminum to magnesium in the lithium-magnesium-aluminum alloy is 5:1 to 15:1. The weight ratio of aluminum to magnesium in the lithium-magnesium-aluminum alloy is 6:1 to 14:1. The weight ratio of aluminum to magnesium in the lithium-magnesium-aluminum alloy is 7:1 to 13:1. The weight ratio of magnesium to aluminum in the lithium-magnesium-aluminum alloy is 8:1 to 12:1. The weight ratio of magnesium to aluminum in the lithium-magnesium-aluminum alloy is 9:1 to 11:1. For example, it may be about 10:1. Such a ratio of Al to Mg in the alloy is desirable in terms of the elastic modulus of the alloy.

[0061] When the lithium-magnesium-aluminum alloy is made into a thin film and the alloy thin film is applied to the negative electrode active material layer, the thickness of the alloy thin film may be 10 μm to less than 200 μm.

[0062] In a specific embodiment, the thickness may be less than 180 μm, less than 160 μm, less than 150 μm, less than 140 μm, less than 130 μm, less than 120 μm, less than 110 μm, less than 100 μm, or less than 90 μm, which is advantageous for providing a sufficient lithium source for battery operation and achieving high energy density.

[0063] On the other hand, the thickness of the alloy thin film may be 0.1 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 75 μm or more, 80 μm or more, 85 μm or more, or 90 μm or more. Such a lower limit is advantageous for providing a sufficient lithium supply source for battery operation and realizing high energy density.

[0064] In a specific embodiment, the alloy thin film may have a thickness of 0.1 μm to 200 μm, 1 μm to 200 μm, 50 μm to 200 μm, 50 μm to 150 μm, 50 μm to 120 μm, 60 μm to 110 μm, 60 μm to 140 μm, 70 μm to 90 μm, 70 μm to 130 μm, 80 μm to 120 μm, 90 μm to 110 μm, 75 μm to 85 μm, about 50 μm to 80 μm or 60 μm to 80 μm, about 100 μm, such as 95 μm to 105 μm. When the thickness of the lithium metal satisfies the above range, it may be easier to realize a high energy density by providing a sufficient lithium supply source for battery operation.

[0065] The lithium-magnesium-aluminum alloy according to the present invention may be monolithic. That is, the lithium-magnesium-aluminum alloy according to the present invention has a uniform concentration of magnesium or aluminum throughout the alloy, and there is no concentration gradient according to the position of the alloy. Furthermore, there is no concentration gradient of magnesium and aluminum in the lithium-magnesium-aluminum alloy according to the present invention. The lithium-magnesium-aluminum alloy according to the present invention may be substantially homogeneous. The lithium-magnesium-aluminum alloy may be homogeneous. The magnesium and aluminum may be uniformly distributed in the lithium-magnesium-aluminum alloy. The lithium-magnesium-aluminum alloy according to the present invention is a substantially homogeneous bulk material, in which the entire bulk material is a continuous phase and homogeneous. That is, Mg and Al are all melted, and the entire bulk is in a completely homogeneous state as a continuous phase with lithium. That is, the lithium-magnesium-aluminum alloy according to the present invention may not include a lithium-based material in a discontinuous phase, such as a particulate form having an alloy shell surrounding a metal (e.g., Li) core.

[0066] 6 and 7 show the results of EDS surface elemental analysis of the cross section of the lithium-magnesium-aluminum alloy of Example 1 of the present invention, and it can be seen that Mg and Al are uniformly detected throughout the entire alloy. That is, the magnesium and aluminum are uniformly distributed in the lithium-magnesium-aluminum alloy. Meanwhile, the Li alloy of the present invention has a detailed structure that changes depending on the content of Mg and Al, and in detail, it shows a uniform β-lithium phase of a BCC (body-centered cubic) structure, or it shows a form in which a part of the site where Li should be in the lithium lattice of the BCC structure is replaced with Mg or Al, or the newly generated Li9Al4 phase is uniformly distributed in the alloy matrix in which a part of the Li lattice of the BCC structure is replaced with Mg.

[0067] The negative electrode according to the present invention may essentially comprise or consist of a lithium-magnesium-aluminum alloy, which may be introduced into the negative electrode according to the present invention in the form of a thin film having a plate-like structure with a predetermined thickness.

[0068] In an alternative embodiment, the negative electrode may include additional components, in particular a current collector (also referred to herein as a "negative current collector"). In one embodiment of the present invention, the negative electrode includes a current collector and a negative active material layer disposed on at least one surface of the current collector, and the negative active material layer may include, essentially include, or consist of the lithium-magnesium-aluminum alloy. The negative electrode may be formed by bonding (e.g., pressing) a current collector and an alloy foil, or by depositing the lithium-magnesium-aluminum alloy on at least one surface of a current collector. Preferably, the current collector and the alloy thin film are directly bonded to each other without adding any other elements between them.

[0069] The negative electrode current collector is not particularly limited as long as it supports the negative electrode active material layer, does not induce chemical changes in the battery, and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon; copper or stainless steel whose surface is treated with carbon, nickel, silver, etc.; aluminum-cadmium alloy, etc. may be used. The current collector may have fine irregularities on its surface to strengthen the bonding force with the alloy, which is the negative electrode active material, and may be a film, sheet, thin film, mesh, net, porous body, foam, or nonwoven fabric. For example, the current collector may be selected from the group consisting of a copper current collector, a porous current collector, and a plastic current collector. The current collector may have a thickness in the range of 1 to 60 μm. For example, when a current collector in the form of a metal thin film is used, the thickness of the current collector may be 1 μm to 20 μm. When the thickness of the current collector satisfies the above range, the current collecting effect can be ensured, and even when the cell is folded and assembled, the processability can be easily ensured.

[0070] The lithium-magnesium-aluminium alloy according to the present invention may have an elastic modulus of 300 MPa or more, 350 MPa or more, 400 MPa or more, 450 MPa or more, 500 MPa or more, 550 MPa or more, 600 MPa or more, or 650 MPa or more.

[0071] The lithium-magnesium-aluminum alloy may have an elastic modulus of 1,000 MPa or less, 900 MPa or less, or 800 MPa or less.

[0072] In a specific embodiment, the lithium-magnesium-aluminum alloy may have an elastic modulus of 300 to 1,000 MPa, 400 to 1,000 MPa, 500 to 900 MPa, 550 to 800 MPa, or 500 to 700 MPa.

[0073] In one embodiment of the present invention, the measurement of the elastic modulus may be in accordance with ASTM standard (ASTM D412-B). ASTM D412-B is used to measure the elasticity of a material under tensile deformation and when the load is removed after testing. The elastic modulus is expressed by a relationship between stress σ and deformation rate ε, and specifically, the measurement method may be described as the following Equation 2.

[0074] Stress (σ) = Elasticity coefficient (E) × Deformation rate (ε) … Equation (2) Here, the stress and elastic modulus are expressed in units of N / mm 2 The deformation ratio can be calculated by the following Equation 3:

[0075] Deformation rate (ε) = deformation (δ) / length (l) ... Equation (3)

[0076] In one embodiment of the present invention, the elastic modulus can be specifically measured by the following method. First, an alloy sample is prepared by punching out an alloy to a predetermined size, and then the measurement is performed using a UTM (Universal Testing Machine) and a load cell of 20N or 100N for each specimen. The UTM equipment is a known one, and for example, an Ametek Ls1 UTM equipment can be used. In one embodiment of the present invention, the size of the sample is preferably in accordance with ASTM D412-B. For example, the size of the sample can be appropriately determined within the range of 80mm to 200mm in width, 10mm to 50mm in length, 30mm to 100mm in width of the straight part at the center of the sample, and 1mm to 12mm in length of the straight part at the center of the sample. In a more specific embodiment, the size of the sample may be about 140 mm wide and about 25 mm long, with the width of the straight portion at the center of the sample being about 60 mm wide and the length of the straight portion at the center of the sample being 6 mm, according to ASTM D412-B. The measurement speed is a single strain rate of 0.01 / s (18 mm / min). Figure 4 is a photograph showing an example of a punch for punching a specimen used in measuring the elastic modulus. The alloy thin film was pressed and cut using the punch of Figure 4.

[0077] The lithium-magnesium-aluminum alloy has a thermal conductivity of at least 450 MPa cm according to the following formula (1): 3 EM / g d The value may be:

[0078] EM d =EM alloy / d alloy ...Formula (1)

[0079] Here, E.M. alloy is the elastic modulus of the lithium-magnesium-aluminum alloy according to the ASTM standard, and d alloy means the density of the lithium-magnesium-aluminum alloy, where the density of the alloy means the mass of the alloy per unit volume of the alloy, the volume being the apparent volume of the alloy.

[0080] The term "apparent volume" is a concept indicating the size or capacity of an external space occupied by an object, and refers to the external size or space not taking into account the actual internal structure or density of a material. The apparent volume can be calculated using measurements such as length, width, and height. For example, the apparent volume of a rectangular parallelepiped object can be calculated by "length x width x height."

[0081] The lithium-magnesium-aluminum alloy has a thermal conductivity of at least 500 MPa cm according to formula (1). 3 EM / g d The lithium-magnesium-aluminum alloy may have a modulus of at least 550 MPa cm according to formula (1). 3 EM / g d The lithium-magnesium-aluminum alloy may have a modulus of at least 575 MPa cm according to formula (1). 3 EM / g d The lithium-magnesium-aluminum alloy may have a thermal conductivity of at least 600 MPa cm according to formula (1). 3 EM / g d The value may be:

[0082] The lithium-magnesium-aluminum alloy has a melting point of 500 to 750 (MPa cm) according to the formula (1). 3 ) / g EM d The lithium-magnesium-aluminum alloy may have a thermal conductivity of 550 to 700 MPa cm according to the formula (1). 3 EM / g d The lithium-magnesium-aluminum alloy may have a thermal conductivity of 575 to 700 MPa cm according to formula (1). 3 EM / g d The lithium-magnesium-aluminum alloy may have a thermal conductivity of 600 to 650 MPa cm according to the formula (1). 3 EM / g d The value may be:

[0083] In one embodiment of the present invention, the lithium-magnesium-aluminum alloy has a tensile strength of 5.0 MPa or less, for example, 3.0 MPa or less, 2.5 MPa or less, or 2.1 MPa or less.

[0084] In one embodiment of the present invention, the lithium-magnesium-aluminum alloy may have a tensile strength of 1.50 MPa or more and 5.0 MPa or less, for example, 1.70 MPa or more and 3.0 MPa or less, 1.90 MPa or more and 2.5 MPa or less, or 1.95 MPa or more and 2.1 MPa or less.

[0085] Meanwhile, the lithium-magnesium-aluminum alloy according to the present invention may have a tensile strength of 1.50 MPa or more, preferably 1.70 MPa or more, more preferably 1.90 MPa or more or 1.95 MPa or more. In the present invention, the tensile strength may be measured by the same method as the above-mentioned elastic modulus measurement method.

[0086] The method for forming the lithium-magnesium-aluminum metal alloy is not particularly limited, and any method for forming a layer or film commonly used in the art may be used, such as a compression method or a coating method.

[0087] The lithium-magnesium-aluminum alloy may include the steps of: a) melting metallic lithium to obtain a lithium molten material; b) adding metallic magnesium and metallic aluminum to the lithium molten material obtained in step a) to obtain a lithium-magnesium-aluminum molten material; c) maintaining the lithium-magnesium-aluminum molten material obtained in step b) at a temperature of 200° C. or higher; d) cooling the lithium-magnesium-aluminum molten material obtained in step c) to obtain a lithium-magnesium-aluminum alloy ingot; and e) producing a lithium-magnesium-aluminum alloy from the lithium-magnesium-aluminum alloy ingot, the alloy in the form of a thin film in one embodiment.

[0088] The method may include placing solid pieces of lithium metal, such as lithium ingots, together with solid pieces of magnesium metal, such as magnesium pellets, and solid pieces of aluminum metal, such as aluminum pellets, in a suitable heating means (e.g., a vessel). The heating means may further include stirring means for stirring the melt of the three metals and means for providing an inert gas atmosphere to the heating means. The step of providing metallic lithium, metallic magnesium, and metallic aluminum (step a)) may not include a sputtering step, such as DC sputtering. Rather, step b) may include stirring the melt. This approach is a more cost-effective method for providing lithium-magnesium-aluminum alloys with much more homogeneous and improved magnesium and aluminum distribution.

[0089] The melting may include heating metallic lithium together with metallic magnesium and metallic aluminum at a temperature between 200°C and 500°C.

[0090] The cooling in step d) may be to room temperature.

[0091] In one embodiment of the present invention, the method for producing the lithium-magnesium-aluminum alloy may include a method for obtaining the lithium-magnesium-aluminum alloy by roll pressing the lithium-magnesium-aluminum alloy ingot. In the roll pressing, heat and pressure may be applied simultaneously, and may be performed using a hot roll press or the like.

[0092] Meanwhile, in one embodiment of the present invention, the method for manufacturing an electrode according to the present invention may further include the following step f) of bonding / adhering the lithium-magnesium-aluminum alloy obtained above to a current collector.

[0093] In one embodiment of the invention, a negative electrode for a lithium-ion secondary battery can be obtained by the method according to the invention.

[0094] In one embodiment of the present invention, a negative electrode for a lithium secondary battery may include an alloy formed by combining lithium with one or more additional metals, wherein the alloy has an elastic modulus of 300 MPa or more according to the above.

[0095] The alloy may have an elastic modulus of at least 300 MPa. The alloy may have an elastic modulus of at least 350 MPa. The alloy may have an elastic modulus of at least 400 MPa. The alloy may have an elastic modulus of at least 450 MPa. The alloy may have an elastic modulus of at least 500 MPa. The alloy may have an elastic modulus of at least 550 MPa. The alloy may have an elastic modulus of at least 600 MPa. The alloy may have an elastic modulus of at least 650 MPa.

[0096] The alloy may have an elastic modulus of 1,000 Mpa or less.The alloy may have an elastic modulus of 900 Mpa or less.The alloy may have an elastic modulus of 800 Mpa or less.

[0097] The alloy may have an elastic modulus of 300Mpa to 1,000Mpa. The alloy may have an elastic modulus of 400Mpa to 1,000Mpa. The alloy may have an elastic modulus of 500Mpa to 900Mpa. The alloy may have an elastic modulus of 550Mpa to 800Mpa. The alloy may have an elastic modulus of 500Mpa to 700Mpa.

[0098] In one embodiment of the invention, a negative electrode for a lithium secondary battery may include an alloy including a combination of lithium and one or more additional metals, where the alloy has a resistance of 600 MPa cm according to the following formula (1): 3 / g or more EM d It has a value.

[0099] EM d =EM alloy / d alloy ...Formula (1) Here, E.M. alloy is the elastic modulus of the alloy according to the ASTM standard, and d alloymeans the density of the alloy, where the density of the alloy means the mass of the alloy per unit volume of the alloy, and the volume is the apparent volume of the alloy.

[0100] The alloy has a compressibility of 500 MPa cm according to formula (1). 3 / g or more Em d The alloy may have a modulus of 550 MPa cm according to formula (1). 3 / g or more Em d The alloy may have a modulus of 575 MPa cm according to formula (1). 3 / g or more Em d The alloy may have a modulus of 600 MPa cm according to formula (1). 3 / g or more Em d The value may be:

[0101] The alloy has a compressibility of 750 MPa cm according to formula (1). 3 / g or less Em d The alloy may have a modulus of 700 MPa cm according to formula (1). 3 / g or less Em d The alloy may have a modulus of 650 MPa cm according to formula (1). 3 / g or less Em d The value may be:

[0102] The alloy has a compressibility of 500 to 750 MPa cm according to formula (1). 3 / g Em d The alloy may have a modulus of 550 to 700 MPa cm according to formula (1). 3 / g Em d According to the formula (1), it can have a value of 575 to 700 MPa cm 3 / g Em d The alloy may have a modulus of 600 to 650 MPa cm according to formula (1). 3 / g Em d The value may be:

[0103] Meanwhile, in one embodiment of the present invention, the alloy may have a tensile strength of 1.50 MPa or more, preferably 1.70 MPa or more, more preferably 1.90 MPa or more or 1.95 MPa or more.

[0104] Meanwhile, in one embodiment of the present invention, the alloy may have a tensile strength of 5.0 MPa or less, for example, 3.0 MPa or less, 2.5 MPa or less, or 2.1 MPa or less.

[0105] In one embodiment of the present invention, the alloy may have a tensile strength of 1.50 MPa or more and 5.0 MPa or less, such as 1.70 MPa or more and 3.0 MPa or less, 1.90 MPa or more and 2.5 MPa or less, or 1.95 MPa or more and 2.1 MPa or less.

[0106] In a specific embodiment of the present invention, the additional metal may include magnesium and / or aluminum. Preferably, the additional metal may be magnesium and aluminum.

[0107] The above object can be achieved by a lithium secondary battery including the negative electrode for lithium secondary batteries according to the present invention. The lithium secondary battery may further include a positive electrode, a separator, and an electrolyte. The lithium secondary battery may be a lithium-sulfur battery.

[0108] The lithium-sulfur battery according to the present invention may further include additional components known in the art in addition to the negative electrode, in particular a positive electrode, a cathode, a separator, and an electrolyte. In particular, the lithium-sulfur battery includes a positive electrode, a negative electrode, and an electrolyte interposed therebetween, and the negative electrode is an anode as described herein.

[0109] The positive electrode may include a positive electrode current collector and a positive electrode active material layer coated on one or both sides of the positive electrode current collector.

[0110] The positive electrode current collector is for supporting the positive electrode active material, and is the same as that described above with respect to the current collector supporting the negative electrode.

[0111] The positive electrode active material layer may include a positive electrode active material, and may further include a conductive material, a binder, an additive, and the like.

[0112] The positive electrode active material may include at least one selected from the group consisting of elemental sulfur (S8) and sulfur compounds. The positive electrode active material may include inorganic sulfur, Li2S n (n≧1), disulfide compounds, organic sulfur compounds and carbon-sulfur polymers ((C2S x )n, x=2.5 to 50, n≧2) Preferably, the positive electrode active material may include inorganic sulfur (S8).

[0113] The sulfur contained in the positive electrode active material does not have electrical conductivity by itself, and therefore may be used together with a conductive material such as a carbon material. Thus, the sulfur may be included in the form of a sulfur-carbon composite, and preferably, the positive electrode active material may be a sulfur-carbon composite.

[0114] The carbon contained in the sulfur-carbon composite may be a porous carbon material, which can provide a skeleton to uniformly and stably fix sulfur and compensate for the low electrical conductivity of sulfur to facilitate an electrochemical reaction.

[0115] The porous carbon material may be prepared by carbonizing various carbonaceous precursors. The porous carbon material may include non-uniform pores, the average diameter of the pores may be in the range of 1 to 200 nm, and the porosity may be in the range of 10 to 90% of the total volume of the porous carbon material. In the present invention, the method for measuring the porosity is not particularly limited as long as it is a known method for measuring porosity. For example, a known Hg porosimeter may be used, or a mercury porosimeter (Micromeritics AUTOPORE V) may be used. Alternatively, the porosity may be measured by the BET (Brunauer-Emmett-Teller) method using nitrogen gas or ASTM D-2873. Alternatively, the porosity of the electrode may be calculated by calculating the true density from the density (apparent density) of the object to be measured, the composition ratio of the material contained in the object to be measured, and the density of each component, and then calculating and measuring the porosity of the electrode from the difference between the apparent density and the true density (net density). For example, the porosity can be calculated by the following formula 1.

[0116] [Formula 1] Porosity (volume%) = {1-(apparent density / true density)} x 100

[0117] The apparent density in the above formula 1 can be calculated from the following formula 2.

[0118] [Formula 2] Apparent density (g / cm 3 ) = (Weight of electrode (g)) / {(Thickness of electrode (cm)) × (Area of ​​electrode (cm 2 ))}

[0119] Apparent density, or bulk density, is a measure of how much space a material occupies per unit volume, including the voids or air spaces contained within it. That is, apparent density includes the material in its solid state and the voids within its volume. Apparent density can be calculated by dividing the mass of a material by its total volume, which includes all the pores and air spaces within the material. The formula for calculating apparent density is:

[0120] (Formula) Apparent density = mass / total volume The mass may be measured using a balance. For materials with regular patterns (e.g., regular cubes, cylinders, etc.), the dimensions may be measured using suitable tools such as tape measures or calipers, which are known methods in the art. For samples with irregular patterns, the volume may be measured by measuring the displacement of the liquid to determine a known change in volume, which may be the same as the volume of the material. Those skilled in the art will be able to apply other known methods to measure the volume and apparent density.

[0121] Net density (true density) refers to the density of a material without taking into account any voids or porosity contained therein. It is the mass of a solid material divided by its actual volume, excluding any void space in said volume. True density may be calculated by dividing the mass of a material by the solid, unoccupied volume of the material. The formula for calculating true density is:

[0122] (Formula) True density = mass / solid volume (void volume is not taken into account)

[0123] Unlike apparent density, true density does not take into account the total volume not including voids and indicates the intrinsic density of a material. True density can be determined by the methods described above or using the gas pycnometer method according to ISO 12154:2014 or other measurement methods known to those skilled in the art.

[0124] If the average pore diameter is smaller than the above range, the pore size is merely at the molecular level, making sulfur impregnation impossible, whereas if the average pore diameter exceeds the above range, the mechanical strength of the porous carbon material is weakened, making it undesirable for application to the manufacturing process of an electrode.

[0125] The shape of the porous carbon material is not particularly limited as long as it is spherical, rod-like, needle-like, plate-like, tubular or bulk-like and can be generally used in lithium-sulfur batteries.

[0126] The porous carbon material has a porous structure or a high specific surface area and may be one commonly used in the art. For example, the porous carbon material may be graphite; graphene; carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite fibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon. Preferably, the porous carbon material may be carbon nanotubes.

[0127] The sulfur-carbon composite may contain 60 to 90 parts by weight, preferably 65 to 85 parts by weight, more preferably 70 to 80 parts by weight of sulfur per 100 parts by weight of the sulfur-carbon composite. If the sulfur content is less than the above range, the content of the porous carbon material in the sulfur-carbon composite increases relatively, and the specific surface area increases, so that the amount of binder used in the manufacture of the positive electrode increases relative to the content of sulfur. Such an increase in the amount of binder used ultimately increases the surface resistance of the positive electrode and acts as an insulator that prevents the passage of electrons, thereby reducing the performance of the battery. On the other hand, if the sulfur content exceeds the above range, the sulfur that cannot be bonded to the porous carbon material aggregates with each other or is re-leached to the surface of the porous carbon material, making it difficult to accommodate electrons and unable to participate in the electrochemical reaction, resulting in a decrease in the capacity of the battery.

[0128] In addition, in the sulfur-carbon composite, sulfur may be located on the surface of the porous carbon material, for example, at least one of the inner and outer surfaces of the porous carbon material. In this case, sulfur may be present in an area of ​​less than 100%, preferably 1 to 95%, more preferably 60 to 90% of the total area of ​​the inner and outer surfaces of the porous carbon material. When sulfur is present on the inner and outer surfaces of the porous carbon material within the above range, it can exhibit the maximum effect in terms of the electron transfer area and wettability with the electrolyte. Specifically, since sulfur is impregnated thinly and uniformly on the inner and outer surfaces of the porous carbon material within the above range, it is possible to increase the area where electrons are transferred and contacted during charging and discharging. When sulfur is located on 100% of the total area of ​​the inner and outer surfaces of the porous carbon material, the carbon material is completely covered with sulfur, which results in poor wettability with the electrolyte and poor contact with the contained electrically conductive material, and therefore electrons cannot be received at the electrode and cannot participate in the electrochemical reaction.

[0129] The method for producing the sulfur-carbon composite is not particularly limited in the present invention, and may be a method commonly used in the art. For example, a method may be used in which sulfur and a porous carbon material are simply mixed and then heat-treated to form a composite.

[0130] In addition to the above, the positive electrode active material may further include a transition metal element, a Group IIIA element, a Group IVA element, a sulfur compound of these elements, and an alloy of these elements with sulfur, as well as one or more additives selected from the components described above.

[0131] The transition metal elements include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., the IIIA group elements include Al, Ga, In, Tl, etc., and the IVA group elements can include Ge, Sn, Pb, etc.

[0132] The sulfur may be contained in an amount of 40 to 95 wt%, preferably 50 to 90 wt%, more preferably 60 to 85 wt%, based on 100 wt% of the positive electrode active material layer constituting the positive electrode. In one embodiment of the present invention, when a sulfur-carbon composite is used as the positive electrode active material, the sulfur-carbon composite may be contained in an amount of 90 to 97 wt%, based on 100 wt% of the positive electrode active material layer. If the content of the positive electrode active material is less than the above range, the electrochemical reaction of the positive electrode is difficult to sufficiently occur. On the contrary, if the content exceeds the above range, the content of the conductive material and the binder described below is relatively insufficient, so that the resistance of the positive electrode increases and the physical properties of the positive electrode are deteriorated.

[0133] The positive electrode active material layer may optionally further include a conductive material that allows electrons to move smoothly within the positive electrode (specifically, the positive electrode active material) and a binder that allows the positive electrode active material to adhere well to a current collector.

[0134] The conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from the current collector to the positive electrode active material. Any conductive material may be used without limitation as long as it has electrical conductivity.

[0135] For example, the conductive material may be graphite such as natural graphite and artificial graphite; carbon black such as Super-P, denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon derivatives such as carbon nanotubes and fullerene; electrically conductive fibers such as carbon fibers and metal fibers; carbon fluorides; metal powders such as aluminum and nickel powder; or electrically conductive polymers such as polyaniline, polythiophene, polyacethylene, and polypyrrole, which may be used alone or in combination.

[0136] The conductive material may be included in an amount of 0.01 to 30% by weight based on the total weight of the positive electrode active material layer constituting the positive electrode. If the content of the conductive material is less than the above range, the movement of electrons between the positive electrode active material and the current collector becomes difficult, resulting in a decrease in voltage and capacity. Conversely, if the content exceeds the above range, the proportion of the positive electrode active material decreases relatively, which may decrease the total energy (charge amount) of the battery. Therefore, it is preferable to determine the content of the conductive material to be an appropriate content within the above range.

[0137] The binder serves to hold the positive electrode active material on the positive electrode current collector and to organically connect the positive electrode active material to increase the bonding strength therebetween, and any binder known in the art may be used.

[0138] For example, the binder may include fluororesin-based binders including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulosic binders including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders, or mixtures or copolymers of two or more thereof.

[0139] The content of the binder may be 0.5 to 30 wt% based on the total weight of the positive electrode active material layer constituting the positive electrode. If the content of the binder is less than 0.5 wt%, the physical properties of the positive electrode may be deteriorated and the positive electrode active material and the conductive material may be peeled off. If the content exceeds the above range, the ratio of the positive electrode active material and the conductive material in the positive electrode may be relatively decreased, and the capacity of the battery may be decreased. Therefore, it is preferable to determine the content of the binder to be an appropriate content within the above range.

[0140] In the present invention, the method for producing the positive electrode is not particularly limited, and any method known to those skilled in the art or various modified methods may be used.

[0141] In one example, the positive electrode may be manufactured by preparing a positive electrode slurry composition containing the above-mentioned components and then coating the slurry on at least one surface of a positive electrode current collector.

[0142] The positive electrode slurry composition includes the positive electrode active material, the conductive material, and the binder, and may further include a solvent other than the above.

[0143] The solvent may be one that can uniformly disperse the positive electrode active material, the conductive material, and the binder. The solvent may be an aqueous solvent, and water is the most preferable. In this case, the water may be distilled water or deionized water. However, the solvent is not necessarily limited thereto, and a lower alcohol that is easily mixed with water may be used as needed. Examples of the lower alcohol include methanol, ethanol, propanol, isopropanol, butanol, etc., and may be used by mixing with water.

[0144] The solvent may be included in a concentration that allows easy coating, and the specific content varies depending on the application method and device.

[0145] The positive electrode slurry composition may further contain, as necessary, substances commonly used in the art for improving its functions, such as a viscosity modifier, a fluidizing agent, and a filler.

[0146] In the present invention, the method of applying the positive electrode slurry composition is not particularly limited. For example, a doctor blade method, a die casting method, a comma coating method, a screen printing method, etc. may be used. In addition, after forming a separate substrate, the positive electrode slurry may be applied onto the positive electrode current collector by pressing or laminating.

[0147] After the coating, a drying process may be performed to remove the solvent. The drying process is performed at a temperature and time that allows the solvent to be sufficiently removed, and the conditions may vary depending on the type of solvent, so are not particularly limited in the present invention. Examples of the drying method may include a drying method using warm air, hot air, or low-humidity air, a vacuum drying method, and a drying method using (far-infrared) radiation or electron beam irradiation. The drying speed may be adjusted so that the solvent is removed as quickly as possible within a speed range in which cracks are not generated in the positive electrode active material layer due to stress concentration and the positive electrode active material layer is not peeled off from the positive electrode current collector.

[0148] After drying, the current collector may be pressed by mold pressing or roll pressing to increase the density of the positive electrode active material in the positive electrode.

[0149] The porosity of the positive electrode, specifically the positive electrode active material layer manufactured by the above-mentioned composition and manufacturing method, may be 50 to 80%, preferably 60 to 75%. If the porosity of the positive electrode is less than 50%, the filling degree of the positive electrode slurry composition including the positive electrode active material, the conductive material, and the binder is too high, and a sufficient amount of electrolyte capable of exhibiting ionic conduction and / or electrical conductivity is not maintained between the positive electrode and the negative electrode, so that the output characteristics or cycle characteristics of the battery are reduced, and the overvoltage and discharge capacity are significantly reduced. On the other hand, if the porosity of the positive electrode is too high, exceeding 80%, there is a problem that the physical and electrical connection with the current collector is reduced, resulting in a reduced adhesive force and a poor reaction, and the increased porosity is filled with electrolyte, resulting in a reduced energy density of the battery. Therefore, the porosity of the positive electrode is appropriately adjusted within the above range.

[0150] In addition, in the positive electrode according to the present invention, the sulfur loading amount, i.e., the mass of sulfur per unit area of ​​the positive electrode active material layer, is 0.5 to 15 mg / cm. 2 , preferably 1 to 10 mg / cm 2 It could be.

[0151] The negative electrode is as described above.

[0152] The electrolyte contains lithium ions, which cause an electrochemical oxidation or reduction reaction at the positive and negative electrodes.

[0153] The electrolyte may be a non-aqueous electrolyte or a solid electrolyte that does not react with lithium metal, but is preferably a non-aqueous electrolyte that includes an electrolyte salt and an organic solvent.

[0154] The electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. The lithium salt can be any salt that is commonly used in electrolytes for lithium secondary batteries. For example, the lithium salt can be LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, LiN(SO2F)2, lithium chloroborane, lithium lower aliphatic carboxylate, tetra-phenyl lithium borate, lithium imide, and the like.

[0155] The concentration of the lithium salt may be 0.2-2M, specifically 0.4-2M, more specifically 0.4-1.7M, depending on various factors such as the exact composition of the electrolyte solvent mixture, the solubility of the salt, the conductivity, the conductivity of the dissolved salt, the charge and discharge conditions of the battery, the operating temperature, and other factors known in the lithium battery field. If the concentration of the lithium salt is less than 0.2M, the conductivity of the electrolyte may be low and the performance of the electrolyte may be reduced. If the concentration of the lithium salt exceeds 2M, the viscosity of the electrolyte may be high and the mobility of the lithium ions may be reduced.

[0156] The organic solvent contained in the non-aqueous electrolyte may be any organic solvent commonly used in lithium secondary battery electrolytes without limitation. For example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc. may be used alone or in combination. Among these, ether compounds may be used as a representative example.

[0157] The ether-based compounds may include acyclic ethers and cyclic ethers.

[0158] For example, the acyclic ether may be at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, deethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

[0159] For example, the cyclic ether may be at least one selected from the group consisting of 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, and isosorbid dimethyl ether, but is not limited thereto.

[0160] Examples of the ester of the organic solvent include, but are not limited to, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, ε-caprolactone, and mixtures of two or more thereof.

[0161] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more thereof.

[0162] Specific examples of the cyclic carbonate compound include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or mixtures of two or more thereof. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC).

[0163] The electrolyte may further include a nitric acid or nitrite-based compound as an additive in addition to the electrolyte salt and organic solvent. The nitric acid or nitrite-based compound forms a stable coating on the lithium metal electrode, which is the negative electrode, thereby improving charge / discharge efficiency.

[0164] The nitric acid or nitrite-based compound is not particularly limited in the present invention, but may be one or more selected from inorganic nitric acid or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2) and ammonium nitrite (NH4NO2); organic nitric acid or nitrite compounds such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, pentyl nitrite and octyl nitrite; organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, and mixtures of selected components thereof, and preferably lithium nitrate is used.

[0165] The electrolyte may be injected at an appropriate stage in the manufacturing process of the electrochemical device depending on the manufacturing process and desired properties of the final product, that is, before assembly of the electrochemical device or at the final stage of assembly of the electrochemical device.

[0166] A separator may further be included between the positive electrode and the negative electrode.

[0167] The separator may be made of a porous non-conductive or insulating material that separates or insulates the positive electrode and the negative electrode and allows lithium ions to be transported between the positive electrode and the negative electrode. The separator may be any material that is used as a separator in a conventional lithium-sulfur battery without any particular limitations. The separator may be an independent member such as a film, or may include a coating layer added to the positive electrode and / or the negative electrode.

[0168] It is preferable that the separator has excellent wettability with respect to the electrolyte and low resistance to ion migration of the electrolyte.

[0169] The separator may be made of a porous substrate. The porous substrate may be any porous substrate commonly used in lithium-sulfur batteries, and may be a porous polymer film, either alone or laminated therewith. For example, a nonwoven fabric having a high melting point, such as glass fiber or polyethylene terephthalate fiber, or a polyolefin-based porous membrane may be used, but is not limited thereto.

[0170] The material of the porous substrate is not particularly limited in the present invention, and any material that is a porous substrate commonly used in electrochemical devices can be used. For example, the porous substrate can be polyolefin such as polyethylene and polypropylene, polyester such as polyethylene terephthalate and polybutylene terephthalate, polyamide, polyacetal, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, poly(p-phenylene benzobisoxazole), polyarylate, etc.

[0171] The thickness of the porous substrate is not particularly limited, but may be 1 to 100 μm, preferably 5 to 50 μm. Although the thickness range of the porous substrate is not particularly limited to the above range, if the thickness is less than the lower limit, the mechanical properties are deteriorated and the separator is easily damaged during use of the battery.

[0172] The average diameter and porosity of the pores in the porous substrate are not particularly limited, but may be 0.001 μm to 50 μm and 10 vol % to 95 vol %, respectively. The method for measuring the porosity may refer to the above-mentioned contents.

[0173] The lithium secondary battery according to the present invention may be manufactured by a conventional winding process, as well as lamination, stacking and folding processes of the separator and electrodes.

[0174] The shape of the lithium secondary battery is not particularly limited, and may be various shapes such as a cylindrical shape, a laminate shape, a coin shape, and the like.

[0175] The present invention also provides a battery module including the above-mentioned lithium-sulfur battery as a unit cell.

[0176] The battery module can be used as a power source for medium to large devices that require high temperature stability, long cycle characteristics, and high capacity characteristics.

[0177] Examples of such medium- to large-sized equipment include, but are not limited to, power tools driven by electric motors; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0178] Specific examples of the present invention will be described below. However, the following examples are merely illustrative of the present invention, and various changes and modifications are possible within the scope of the present invention, and it will be obvious to those skilled in the art that such changes and modifications are also included within the scope of the present invention.

[0179] Production example 1: Li-Mg-Al alloy production A lithium ingot was melted at a temperature of 200° C. to obtain a lithium melt. A solid magnesium source (pellets) and a solid aluminum source (pellets) were added to the lithium melt to obtain a lithium-magnesium-aluminum melt. The magnesium content was 5 wt % based on the total weight of the lithium-magnesium-aluminum melt (100 wt %). The aluminum content was 0.5 wt % based on the total weight of the lithium-magnesium-aluminum melt.

[0180] The resulting molten material was cooled to room temperature (about 22° C.) to obtain a lithium-magnesium-aluminum alloy ingot. The lithium-magnesium-aluminum alloy ingot was roll-pressed to produce a lithium-magnesium-aluminum alloy in the form of a thin film having a thickness of 80 μm.

[0181] Production example 2 (Li-Zn alloy production) A lithium ingot was melted at a temperature of 200° C. to obtain a lithium melt. A solid Zn source (pellets) was added to the lithium melt to obtain a lithium-Zn melt. The Zn content of the lithium-Zn melt was 5 wt % relative to the total of 100 wt %.

[0182] The obtained molten material was cooled to room temperature (about 22° C.) to obtain a lithium-Zn alloy ingot, which was then roll-pressed to produce a lithium-Zn alloy thin film having a thickness of 80 μm.

[0183] Production example 3 (Li-Al alloy production) A lithium ingot was melted at a temperature of 200° C. to obtain a lithium melt. A solid aluminum source (pellets) was added to the lithium melt to obtain a lithium-aluminum melt. The content of the aluminum was 0.5 wt % relative to the total weight of the lithium-aluminum melt (100 wt %).

[0184] The resulting molten material was cooled to room temperature (about 22° C.) to obtain a lithium-aluminum alloy ingot, which was then roll-pressed to produce a lithium-aluminum alloy thin film having a thickness of 80 μm.

[0185] Production example 4 (Li-Mg alloy production) A lithium ingot was melted at a temperature of 200° C. to obtain a lithium melt. A solid magnesium source (pellets) was added to the lithium melt to obtain a lithium-magnesium melt. The magnesium content was 5 wt % based on the total weight of the lithium-magnesium melt (100 wt %).

[0186] The obtained melt was cooled to room temperature (about 22° C.) to obtain a lithium-magnesium alloy ingot, which was then roll-pressed to produce a lithium-magnesium alloy in the form of a thin film having a thickness of 80 μm.

[0187] Example 1 The 80 μm-thick lithium-magnesium-aluminum alloy thin film obtained in Preparation Example 1 was used as the negative electrode, and no separate current collector was used.

[0188] A slurry was prepared by mixing 4 parts by weight of styrene butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3) as a binder with 96 parts by weight of sulfur / carbon composite (S:C=75:25 parts by weight) as a positive electrode active material, and the slurry was applied to both sides of an aluminum current collector, dried at 50°C for 12 hours, and then roll pressed to prepare a positive electrode. The loading amount of the positive electrode active material in the positive electrode was 2.70 mAh / cm. 2 The porosity was 78 vol%.

[0189] A 16 μm porous polyethylene film (porosity: 68 vol%) was used as the separation membrane.

[0190] A total of seven positive electrodes and eight negative electrodes were inserted, and a porous polyethylene separator was laminated and folded to assemble the cell. A pouch cell was manufactured by inserting the positive and negative electrode tabs into a pouch, injecting electrolyte, and sealing it. The manufactured lithium-sulfur battery was operated at a temperature of 25°C under 0.3C charge / 2.0C discharge conditions to confirm the cycle life and efficiency. The electrolyte was manufactured by adding 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) to a mixture of 1,3-dioxolane and dimethyl ether (DOL:DME=1).

[0191] Comparative Example 1 A lithium-sulfur battery was fabricated in the same manner as in Example 1, except that a lithium thin film having a thickness of 80 μm was used as the negative electrode.

[0192] Comparative Example 2 A lithium-sulfur battery was prepared in the same manner as in Example 1, except that the lithium-zinc alloy having a thickness of 80 μm obtained in Preparation Example 2 was used as the negative electrode.

[0193] Comparative Example 3 A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the lithium-aluminum alloy having a thickness of 80 μm obtained in Preparation Example 3 was used as the negative electrode.

[0194] Experimental evaluation 1: Pouch cell evaluation The lithium-sulfur batteries manufactured in Example 1 and Comparative Examples 1 to 3 were operated at 25°C, 0.3C charge / 2.0C discharge conditions, in the voltage range of 1.8V to 2.5V (vs. Li / Li+), and cycle life and coulombic efficiency were confirmed by a constant current test method. Measurements of battery charge / discharge and coulombic efficiency were performed using a battery charger / discharger (Wonik Pne Co., Ltd.). Specific capacity was calculated by the ratio of the battery discharge capacity (in mAh units) confirmed by the charger / discharger to the weight of sulfur contained in the positive electrode. Coulombic efficiency is the percentage ratio of discharge capacity to charge capacity.

[0195] As can be seen from FIG. 1, when the negative electrode of the lithium-magnesium-aluminum three-phase alloy was applied (Example 1), the cycle life was superior to that of the lithium-sulfur battery using lithium as the negative electrode (Comparative Example 1).

[0196] When the lithium-magnesium-aluminum alloy negative electrode according to the present invention was used (Example 1), the cycle life was superior to that of lithium-sulfur batteries using other dissimilar metal-lithium alloys as the negative electrode (Comparative Examples 2 and 3).

[0197] As shown in FIG. 2, when the lithium-magnesium-aluminum alloy negative electrode according to the present invention is applied (Example 1), the stability of the coulombic efficiency is higher than that of Li metal (Comparative Example 1) and lithium and other heterogeneous metal alloys (Comparative Examples 2 and 3).

[0198] Experimental evaluation 2: Measurement of elastic modulus and tensile strength As shown in Figure 3, Li metal and Li-Mg alloy (Production Example 4) have similar elastic modulus, and the elastic modulus of the Li-Mg-Al alloy of the present invention (Production Example 1) is more than twice as large. Even when considering the elastic modulus relative to the density of the material, the mechanical properties of the Li-Mg-Al material of the present invention are still very good, as shown in Table 1.

[0199] [Table 1]

[0200] The elastic modulus and tensile strength were measured as follows. First, the lithium metal electrodes obtained in Preparation Example 1 and the alloy electrodes obtained in Preparation Example 4 were punched out to a predetermined size to prepare samples, and measurements were performed using a universal testing machine (UTM) and a load cell of 20N or 100N for each specimen. The measurement conditions were a single strain rate of 0.01 / s (18mm / min).

[0201] Experimental evaluation 3: Surface observation A cross section of the lithium-magnesium-aluminum alloy thin film obtained in Preparation Example 1 was obtained by ion milling, and the cross section was observed using a scanning electron microscope (SEM), which is shown in Figure 5. Referring to Figure 5, it was confirmed that the cross section of the obtained alloy thin film exhibited a uniform morphology. The SEM equipment used was a JOEL KOREA JSM-7200F, and the resolution was 3.0 nm (15 kV, WD 10 mm, probe current 5 nA).

[0202] Experimental evaluation 4: EDS measurement results As a result of EDS analysis of the alloy of Preparation Example 1, it was confirmed that magnesium and aluminum were distributed over the entire surface of the negative electrode. Figure 6 is an EDS analysis photograph confirming the distribution of magnesium in the alloy of Preparation Example 1, and Figure 7 is an EDS analysis photograph confirming the distribution of aluminum. The EDS analysis was performed using an Ultim Max 65 under the conditions of 15 kV, WD 10 mm, and probe current 5 nA.

[0203] The features disclosed in the foregoing description and in the dependent claims may, both individually and in any combination thereof, be material for realising the aspects of the disclosure as recited in the independent claims in diverse forms thereof.

Claims

1. A negative electrode for a lithium secondary battery comprising a lithium (Li)-magnesium (Mg)-aluminum (Al) alloy.

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the content of magnesium (Mg) in the lithium-magnesium-aluminum alloy is 0.1 wt % or more and 50 wt % or less, based on a total of 100 wt % of the lithium-magnesium-aluminum alloy.

3. 3. The negative electrode for a lithium secondary battery according to claim 1, wherein the content of aluminum in the lithium-magnesium-aluminum alloy is 0.01 wt % to 10 wt % based on the total weight of the lithium-magnesium-aluminum alloy.

4. 4. The negative electrode for a lithium secondary battery according to claim 1, wherein in the lithium-magnesium-aluminum alloy, a weight ratio of magnesium to aluminum is from 2:1 to 20:

1.

5. 5. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode contains a thin-film lithium-magnesium-aluminum alloy and has a thickness of 0.1 μm or more and 200 μm or less.

6. 6. The negative electrode for a lithium secondary battery according to claim 1, wherein the lithium-magnesium-aluminum alloy has a modulus of elasticity of 400 MPa or more or a tensile strength of 1.5 MPa or more.

7. The lithium-magnesium-aluminum alloy is an EM alloy having the following formula (1): d Value is 600 MPa cm 3 The negative electrode for a lithium secondary battery according to claim 1 , wherein the anode has a Mo content of 1 / g or more. Formula (1) EM d =EM alloy / d alloy Here, E.M. alloy is the elastic modulus of the alloy according to the ASTM standard, and d alloy means the density of an alloy, the density of the alloy means the mass of the alloy per unit volume of the alloy, and the volume is the apparent volume of the alloy.

8. 8. The negative electrode for a lithium secondary battery according to claim 1, wherein the lithium-magnesium-aluminum alloy has a monolithic nature.

9. 9. The negative electrode for a lithium secondary battery according to claim 1, wherein the lithium-magnesium-aluminum alloy has magnesium and aluminum uniformly distributed in the alloy.

10. A negative electrode for a lithium secondary battery comprising an alloy comprising a combination of lithium and one or more additional metals, the alloy having an elastic modulus of 400 MPa or greater.

11. The alloy includes an alloy of lithium in combination with one or more additional metals, the alloy being an EM d The value is 600MPa cm 3 / g or more. Formula (1) EM d =EM alloy / d alloy Here, E.M. alloy is the elastic modulus of the alloy according to the ASTM standard, and d alloy means the density of an alloy, the density of the alloy means the mass of the alloy per unit volume of the alloy, and the volume is the apparent volume of the alloy.

12. A lithium secondary battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the one according to any one of claims 1 to 11.

13. The lithium secondary battery according to claim 12, wherein the lithium secondary battery is a lithium-sulfur battery in which a positive electrode active material contains sulfur (S) and / or a sulfur (S) compound.

14. A method for producing a negative electrode for a lithium secondary battery according to any one of claims 1 to 9, comprising the steps of: Melting metallic lithium to obtain a first melt; adding metallic magnesium and metallic aluminum to the lithium melt to obtain a second melt; maintaining the second molten material at a temperature of 200° C. or more to alloy the second molten material; and cooling the second molten material obtained in the alloying step to obtain a lithium-magnesium-aluminum alloy.

15. The method of claim 14, further comprising the step of obtaining the alloy in an ingot form and thinning the ingot into a plate-like structure having a predetermined thickness.

Citation Information

Patent Citations

  • Multi-element lithium-magnesium alloy negative electrode material for high-cycle-stability secondary battery and adaptive electrolyte thereof

    CN110797524A

  • solid electrolyte and battery

    JP1996508850A

  • Electrode material in the form of a lithium-based alloy and a method for producing same - Patent Application 20070122997

    JP2020530937A

  • KR2016-0034183

  • KR2016-0052351